Cost efficiency of investment and innovation projects of oil processing: methodical aspects - E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность", 2019)
From a position of the transformational processes in modern economy having the innovation basis and, caused by the influence of fourth industrial revolution, the relevance and an entity of the investitsion-but-innovation projects (IIPN) and programs of oil processing are presented, contrastive analysis of static and dynamic approaches to assessment of cost efficiency of IIPN is given, informative features of the dynamic valuation method of cost efficiency of IIPN are revealed